Feasibility of noninvasive near-infrared spectroscopy monitoring in predicting the prognosis of spontaneous intracerebral hemorrhage - Sun, Zhen; Liu, Jing; Wang, Kunpeng; Zhang, Jiandang; Liu, Sujie; Xue, Fei (Frontiers in Neurology, 2024)
Objective: This study aimed to assess the impact of multimodal monitoring on predicting the prognosis of patients with spontaneous intracerebral hemorrhage (SICH) and to examine the feasibility of using noninvasive near-infrared spectroscopy (NIRS) for monitoring clinical prognosis.: Clinical data of 38 patients with SICH who underwent surgery in the Department of Neurosurgery of Shaanxi Provincial People's Hospital from May 2022 to December 2022 were retrospectively analyzed. The patients were categorized into two groups based on the Glasgow Outcome Scale (GOS) 3 months after operation: poor outcome group (GOSI-III) and good outcome group (GOSIV and V). Multimodal monitoring included invasive intracranial pressure (ICP), brain temperature (BT), internal jugular venous oxygen saturation (SjvO2), and noninvasive NIRS. NIRS monitoring comprised the assessment of brain tissue oxygen saturation (StO2), blood volume index (BVI), and tissue hemoglobin index (THI). The prognostic differences between the two groups were compared. The predictive values were evaluated using the receiver operating characteristic (ROC) curve and the area under the curve (AUC).Results: ICP、 BT、 BVI and THI in the good prognosis group were lower than those in the poor prognosis group. The SjvO2 and StO2 in the group with a good prognosis were higher than those in the group with a poor prognosis.The levels of ICP, BT, SjvO2, StO2, BVI, and THI reflect the changes in brain function and cerebral blood flow and significantly correlate with the prognosis of patients with SICH. NIRS monitoring has a high clinical utility in assessing the prognosis.